Nilai parameter kadar pencemar sebagai penentu tingkat efektivitas tahapan pengolahan limbah cair industri batik lilin - Indrayani Indrayani; Nur Rahmah (Jurnal Rekayasa Proses, 2018)
Batik industry sector has a strategic role in development, especially to increase the level of employment and its contribution in encouraging the growth of creative economy. Along with the development of batik industry that has been known globally, batik industry produces a negative impact of liquid waste in a large amount which will potentially pollute the environment. This paper described the characteristics of batik industrial wastewater and its treatment stages both in physics, chemistry and biology. The treated wastewater is analyzed and adjusted to the required wastewater quality standard parameters. The wastewater treatment plant in Balai Besar Kerajinan dan Batik (BBKB) consist of physical process i.e. sedimentation, biological process i.e. anaerobic treatment and chemical process i.e. coagulation. The efficiency of the process is determined by the value of test results at each stage of wastewater treatment. The efficiency of physical, biological and chemical process in this plant were 71.69%; 55,31%; 40.75%, respectively. According to the results, the treated wastewater could be discharged safely to the environment.